TRANSFORMASI KAJIAN KEISLAMAN PADA LEMBAGA DAKWAH KAMPUS (LDK) JUNDULLAH IAIN PALU - Mariam Mariam; Syamsuri Syamsuri; Mansur Mangasing (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2017)
LDK Jundullah is organization of da’wah (Islamic preaching) in IAIN Palu that has concerned with Islamic studies. Therefore, students and also community can understand Islam as a religion that is able to form a good character. In addition, Islamic studies can be alternative to relieve a boredom for society due to the emergence of new schools in Islam that are in contradicton with the Quran and Sunnah. This organization carry out activities such as organizing seminars, training of preacher, weekly meeting (liqo), two-level training (daurah) for new comers, female Muslim activities, and economic empowerment. The activities done by the activists of LDK Jundullah are focused on good character and exemplary in campus and society.